Kinetic studies on hydrolysis of urea in a semi-batch reactor at atmospheric pressure for safe use of ammonia in a power plant for flue gas conditioning - Mahalik, K.; Sahu, J.N.; Patwardhan, A.V.; Meikap, B.C. (Elsevier, 2010)
With growing industrialization in power sector, air is being polluted with a host of substances-most conspicuously with suspended particulate matter emanating from coal-fired thermal power plants. Flue gas conditioning, especially in such power plants, requires in situ generation of ammonia. In the present paper, experiments for kinetic study of hydrolysis of urea have been conducted using a borosil glass reactor, first without stirring followed by with stirring. The Study reveals that conversion increases exponentially with an increase in temperature and feed concentration. Furthermore. the effect of stirring speed, temperature and concentration on conversion has been studied. Using collision theory. temperature dependency of forward rate constant has been developed from which activation energy of the reaction and the frequency factors have been calculated. It has been observed that the forward rate constant increases with an increase in temperature. The activation energy and frequency factor with stirring has been found to be 59.85 kJ/mol and 3.9 x 10(6) min(-1) respectively with correlation co-efficient and standard deviation being 0.98% and +/- 0.1% in that order. (C) 2009 Elsevier B.V. All rights reserved.